(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s population is about to undergo significant changes in terms of age and demographics. In particular, estimates have shown a rise in the proportion of old people and people with dementia-related diseases. The demographics of ageing, its effect on the healthcare system, and suggested measures to better serve the elderly have all been explored in earlier research. An overview of these findings in regard to important aged care players, such as mental health professionals, informal carers, and public health officials, is the main emphasis of this paper. We draw the general conclusion that all stakeholders have a limited understanding of what pathological ageing (i.e., dementia) is, which has a number of negative consequences including holding up the process of seeking treatment and making it difficult to conduct and have accurate demographic studies. Furthermore, filling this knowledge gap can improve communication between these three parties in the hopes of achieving the following goals: (a) greater education and awareness; (b) quicker care seeking; and (c) earlier diagnoses providing better opportunities to gather accurate demographic data on people with dementia-related disorders.